Membangun Masyarakat Berkepribadian di Bidang Kebudayaan dalam Memperkuat Jawa Tengah sebagai Pusat Kebudayaan Jawa - Eko Punto Hendro (Endogami: Jurnal Ilmiah Kajian Antropologi, 2018)
THE -- condition of the Javanese society is now more individualistic, materialistic, and more prioritizing its own interests than the common interest, the lack of tolerance towards others, wanting to get rich by justifying all means, as well as violence and crime is increasing everywhere. Aspects of power and economic aspects become very dominant in the orientation of community life, which should only be a means of living together. As a result, today's society tends to pursue wealth and power by justifying all means, ignorance, and leaving mutual cooperation and tolerance.Soekarno's trilogy program implemented by the Governor of Central Java with the addition of "ora ngapusi" and "ora korupsi" slogan, may be appreciated by the people of Central Java, especially to improve people's understanding of their adhilugung culture.